Innovations in Food Trade : Rethinking Aflatoxin Management in East Africa - Keyser, John C.; Sela, Shane (World Bank, Washington, DC, 2020)
The high prevalence of aflatoxins in maize and other staple foods in the EAC has become an important obstacle to domestic and regional food trade. While EAC Member States have made good progress in promulgating regionally harmonized standards that include mandatory upper limits on aflatoxins, the high cost and complexity of meeting these standards has led to a large share of food being traded outside the regulatory framework thereby distancing poor producers from the market and undermining the prospects for regional value chain development. Especially as EAC countries look to recover from COVID-19 (coronavirus) and build resilient food systems for the future, minimizing the cost of market transactions is more important than ever. The need for aflatoxin management begins at the farm level where fundamental challenges with smallholder agriculture make crops highly susceptible to contamination.1 Bimodal rainfall across much of the EAC make sun drying and storage difficult and poor post-harvest practices such as hand shelling of grain and drying of crops directly on the ground compound the problem. Simple improvements in these areas are possible but add to cost so can be difficult for poor farmers and traders to justify without adequate incentives. As awareness of aflatoxins grows in the EAC, many farmers are adopting improved practices on crops saved for family consumption but not for market sale. Current regulatory approaches to managing aflatoxins in the EAC rely on expensive testing and border controls that are easily circumvented. In Uganda, SPS procedures now require exporters to submit a certificate of aflatoxin analysis from one of three nationally recognized laboratories for every consignment. Throughout the EAC, tests happen far away from the main production areas and only large firms have the wherewithal to comply. Similarly, at the consumer end of domestic and regional value chains, only large industrial mills perform regular tests and are subject to routine inspection. Meanwhile, small traders and SMEs can navigate around the regulatory system since borders are porous and small mills are rarely inspected. This situation not only leaves the EAC with little to no effective control over aflatoxins but precludes the payment of premiums to small farmers and offtakers that are needed to reward improvements at upstream stages of the value chain where aflatoxin problems begin.